Elaboración de un plan estratégico de continuidad en el servicio eléctrico para la ciudad de manta provincia de Manabí - Salazar Pozo, Julio Ernesto (2009)
The following work tries in the elaboration of a Plan of Continuity of the Business to Distribute electric power in a continuous way for the city of Manta, being based in the summary of historical information of the Departmental Directions, corresponding to the period 2000 - 2008, of the National Corporation of Electricity Regional Manabí (CNEL-Manabí).” In spite of the fact that the stages for the creation of a program of continuity of the business (BCP) they are different in each organization, the final goal is the same one: to establish a program that it will prevent or it will reduce in great scale any type of labor interruption. The methodology used for business continuity allows the alignment from the process to the best practices in the industry. This is, the following the cycle of continuous improvement that begins with the one: Analysis, the design, implementation and revision of the processes, risks or threats. Desafortunamente in our country is not very extended the culture of the prevention. The culture of the gliding of disasters is not very common. The first great obstacle that faced in CNEL-Manabí that a BCP has not implanted is the ignorance. The second difficulty to conquer the lack of clear and official procedures.